A companion to the history of the book - Eliot, Simon; Rose, Jonathan (Blackwell companions to literature and culture ;, 2009)
From the early Sumerian clay tablet through to the emergence of the electronic text, this Companion provides a continuous and coherent account of the history of the book. --from publisher description